2017
DOI: 10.3390/en10111846
|View full text |Cite
|
Sign up to set email alerts
|

Battery Energy Management in a Microgrid Using Batch Reinforcement Learning

Abstract: Abstract:Motivated by recent developments in batch Reinforcement Learning (RL), this paper contributes to the application of batch RL in energy management in microgrids. We tackle the challenge of finding a closed-loop control policy to optimally schedule the operation of a storage device, in order to maximize self-consumption of local photovoltaic production in a microgrid. In this work, the fitted Q-iteration algorithm, a standard batch RL technique, is used by an RL agent to construct a control policy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 28 publications
0
96
0
7
Order By: Relevance
“…Figure depicts the comparisons between efficiencies of the controlled inverter topology and the conventional inverter topologies depicted in previous studies . It is observed that the efficiency of the proposed inverter is higher than that of the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Figure depicts the comparisons between efficiencies of the controlled inverter topology and the conventional inverter topologies depicted in previous studies . It is observed that the efficiency of the proposed inverter is higher than that of the literature.…”
Section: Resultsmentioning
confidence: 99%
“…They treat the MG as a black box and find a near-optimal strategy from interactions with it. For instance, Brida et al [18] developed a battery energy management strategy for a MG by using the batch RL technology. Sunyong et al [19] proposed a RL-based EMS for a MG-like smart building to reduce the operating cost.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the conventional distributed methods, learning-based methods can be easily adapted with a real-time problem after the off-line training process. In RL, Q-learning is a popular method and is widely used for the optimal operation of microgrids [19][20][21][22][23]. A fitted Q-iteration-based algorithm has been proposed in [19] for a BESS.…”
Section: Introductionmentioning
confidence: 99%
“…In RL, Q-learning is a popular method and is widely used for the optimal operation of microgrids [19][20][21][22][23]. A fitted Q-iteration-based algorithm has been proposed in [19] for a BESS. A data-driven method is utilized in [19] and it uses a state-action value function to optimize a scheduling plan for the BESS in grid-connected mode.…”
Section: Introductionmentioning
confidence: 99%